Complex Automated Negotiations: Theories, Models, and Software Competitions - Ito, Takayuki; Zhang, Minjie; Robu, Valentin; Matsuo, Tokuro; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Complex Automated Negotiations are a widely studied, emerging area in the field of Autonomous Agents and Multi-Agent Systems. In general, automated negotiations can be complex, since there are a lot of factors that characterize such negotiations. For this book, we solicited papers on all aspects of such complex automated negotiations, which are studied in the field of Autonomous Agents and Multi-Agent Systems. This book includes two parts, which are Part I: Agent-based Complex Automated Negotiations and Part II: Automated Negotiation Agents Competition. Each chapter in Part I is an extended version of ACAN 2011 papers after peer reviews by three PC members. Part II includes ANAC 2011 (The Second Automated Negotiating Agents Competition), in which automated agents who have different negotiation strategies and implemented by different developers are automatically negotiate in the several negotiation domains. ANAC is an international competition in which automated negotiation strategies, submitted by a number of universities and research institutes across the world, are evaluated in a tournament style. The purpose of the competition is to steer the research in the area of bilateral multi-issue, closed negotiation. This book includes rules, results, agents and domains descriptions for ANAC2011 submitted by organizers and finalists.
Keywords: Engineering; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).